Operations management and the resource based view: Another view - Bromiley, Philip; Rau, Devaki (Journal of Operations Management, 2016)
AbstractThis paper evaluates the usefulness of the resource‐based view (RBV) to the field of operations management. Based on the seminal RBV articles, we argue that using the RBV does not align with the objectives and activities of operations management researchers in several ways. First, the dependent variable in the RBV is sustained competitive advantage. Using sustained competitive advantage as a dependent variable implies that scholars focus on explaining the differences between the relatively few firms with sustained competitive advantage and all the other firms, ignoring performance variations within the great mass of firms. In addition, competitive advantage exists at the level of the business or the firm and does not directly translate into the normal level of operations management research. Measuring sustained competitive advantage also presents difficulties. Second, the explanatory variables in the RBV are resources that must be rare, valuable and hard or impossible to imitate. Measuring valuable resources or factors firms cannot imitate poses serious problems both in demonstrating value independent of the factor's impact on performance (i.e., avoiding tautology) and in measuring unique or nearly unique entities. Third, under the RBV, prescription is problematic; you cannot prescribe things that firms can readily implement because such things can be imitated. We present the practice‐based view (PBV) as a simpler and better alternative for operations management where scholars attempt to explain the entire range of firm and unit performance based on transferable practices.